(untitled) (International journal of artificial intelligence, 2025)
This article explores the psychological features of emotional intelligence development in future teachers. Emotional intelligence (EI) is a vital factor in the professional formation of teachers, influencing their communication, empathy, self-regulation, and decision-making skills. The paper analyzes the psychological mechanisms that contribute to the development of emotional intelligence among pedagogical students and emphasizes its importance in effective teaching and classroom management.